Speckle correlation as a monitor of X‐ray free‐electron laser induced crystal lattice deformation. (9th October 2020) - Plumley, Rajan; Sun, Yanwen; Teitelbaum, Samuel; Song, Sanghoon; Sato, Takahiro; Chollet, Matthieu; Nelson, Silke; Wang, Nan; Sun, Peihao; Robert, Aymeric; Fuoss, Paul; Sutton, Mark; et al.
Abstract : Free‐electron laser X‐ray beam‐induced lattice disorder is investigated by measuring shot‐to‐shot evolution of near‐Bragg coherent diffuse scattering from single‐crystal germanium. It is shown that X‐ray photon correlation analysis of sequential speckle measurements can be used to monitor the nature and extent of the lattice displacement rearrangement. Abstract : X‐ray free‐electron lasers (X‐FELs) present new opportunities to study ultrafast lattice dynamics in complex materials. While the unprecedented source brilliance enables high fidelity measurement of structural dynamics, it also raises experimental challenges related to the understanding and control of beam‐induced irreversible structural changes in samples that can ultimately impact the interpretation of experimental results. This is also important for designing reliable high performance X‐ray optical components. In this work, X‐FEL beam‐induced lattice alterations are investigated by measuring the shot‐to‐shot evolution of near‐Bragg coherent scattering from a single crystalline germanium sample. It is shown that X‐ray photon correlation analysis of sequential speckle patterns measurements can be used to monitor the nature and extent of lattice rearrangements. Abrupt, irreversible changes are observed following intermittent high‐fluence monochromatic X‐ray pulses, thus revealing the existence of a threshold response to X‐FEL pulse intensity.